Lessons for the future : the missing dimension in education - Hicks, David, 1942- (Futures and education series., 2003)
In Lessons for the Future, Davis Hicks provides an insight into, and an argument for, futures education. He discusses the latest innovative teaching and research in the field and looks at young people's attitudes to the future.